Active Site Labeling of Fatty Acid and Polyketide Acyl-Carrier Protein Transacylases - Davis, Tony D. (Org Biomol Chem, 2019)
Metabolic engineering of fatty acids and polyketides remains challenging due to unresolved protein-protein interactions that are essential to synthase activity. While several chemical probes have been developed to capture and visualize protein interfaces in these systems, acyl carrier protein (ACP) transacylase (AT) domains remain elusive. Herein, we combine a mutational strategy with fluorescent probe design to expedite the study of AT domains from fatty acid and polyketide synthases. We describe the design and evaluation of inhibitor-inspired and substrate-mimetic reporters containing sulfonyl fluoride and β-lactone warheads. Moreover, specific active-site labeling occurs by optimizing pH, time, and probe concentration, and selective labeling is achieved in the presence of inhibitors of competing domains. These findings provide a panel of AT-targeting probes and set the stage for future combinatorial biosynthetic and drug discovery initiatives.